KAJIAN TAFSIR TEMATIK KONTEMPORER: Analisis Terhadap Metode Tafsir Tematik Ayat-ayat Psikologis Karya Moh. Abdul Kholiq Hasan - Ervi Marafaniza; Moh. Abdul Kholiq Hasan (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2023)
Thematic interpretation of psychological verses is the work of Moh. Abdul Kholiq Hasan published after Tafsir Rabbana. This interpretation is written to to form it simpler for somebody to get it the relationship of verses in the Quran. In the context of thematic interpretation of psychological verses, this method will help gain a deeper understanding of the psychological themes contained in the Quran. For example, psychological themes such as anxiety, sadness, happiness, and trust can be analyzed in detail and in depth through the thematic interpretation method. The consider looks for to clarify the mental travel of the mufassir, the works of the mufassir and the comes about of the examination of the topical translation strategy of mental verses. The results of this study explain that Hasan wrote this work because of the demands as a lecturer and became an alternative for students who are not accustomed to reading the interpretation of the Koran as a whole because the method used is thematic which examines verses with certain themes and uses psychological patterns.